Kaposi's sarcoma after T‐cell costimulation blockade with abatacept in rheumatoid arthritis: a case report. (6th March 2017) - Olivo, D.; Grembiale, R. D.; Tallarigo, F.; Russo, E.; De Sarro, G.; Ursini, F.
Summary: What is known and objective: Kaposi's sarcoma (KS) is a malignant neoplasm caused by HHV‐8, a pathogen that leads to endothelial cell transformation when host defences are weakened. Case description: Here we report the first case of KS during treatment with abatacept, a biologic agent targeting T‐cell costimulation. The patient was a 64‐year‐old female with rheumatoid arthritis who developed multiple firm, purple‐reddish nodules on the dorsal aspect of the right hand. Histological examination confirmed KS. What is new and conclusion: Although a direct causal relationship between KS development and abatacept treatment cannot be proved, we hypothesize a role for costimulation blockade. Abstract : Schematic representation of the hypothetical mechanism leading to KS development in our patient. Unrecognized HHV‐8 infection could induce CD80/86 downregulation in endothelial cells; the superimposed CD80/86 blockade after treatment with abatacept could subsequently abrogate T cell recognition of infected cells and open the way for malignant transformation.